Effect of Black Cumin Extract (Nigella sativa Linn.) on Closure Time of Incision Wound in Swiss Webster Mice - Febrianto, Verent; Bulan, Susanti; Lesmana, Dian (e-GiGi, 2022)
Abstract: Incision wounds in dentistry can be caused by several procedures inter alia incision of abscess, odontectomy, extraoral incision, parotidectomy, and others. Certain drugs are needed to accelerate wound healing and prevent infection. Generally, anti-inflammatory drugs such as steroids and non-steroids are given to accelerate wound healing. Herbal remedies such as black cumin extract can also be an alternative to be applied topically. This study aimed to evaluate the effect of black cumin extract on closure time of incision wound on the back of male Swiss Webster mice. This was a laboratory and experimental study. Subjects were 36 Swiss Webster mice divided into two groups. Incision wounds were performed on the back of each subjects. Group I was not given any treatment meanwhile group II was treated with topical application of black cumin extract. The Mann Whitney test showed that the mean wound closure time of group II was 9.7 days, meanwhile of group I was 12.7 days (p=0.0000855). In conclusion, there was a significant effect of black cumin extract on the closure time of the incision wound on the back of Swiss Webster mice which resulted in the fastest complete wound closure on the 8th day.Keywords: black cumin extract; wound closure time Abstrak: Luka insisi dalam bidang kedokteran gigi dapat disebabkan oleh berbagai prosedur, seperti insisi abses, odontektomi, insisi ekstraoral, parotidektomi, dan sebagainya. Pemberian obat diperlukan untuk mempercepat penyembuhan luka dan mencegah terjadinya infeksi. Umumnya, obat anti-inflamasi seperti steroid maupun nonsteroid dapat diberikan untuk mempercepat penyembuhan luka. Obat herbal seperti ekstrak jintan hitam dapat menjadi alternatif yang diaplikasikan secara topikal. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak jintan hitam terhadap waktu penutupan luka insisi pada punggung mencit Swiss Webster jantan. Jenis penelitian ialah eksperimental laboratorik. Subyek penelitian berjumlah 36 ekor mencit Swiss Webster jantan yang dibagi menjadi dua kelompok. Semua subyek dibuat luka insisi pada punggung. Kelompok I tidak diberikan perlakuan sedangkan kelompok II diberi perlakuan aplikasi ekstrak jintan hitam secara topikal. Hasil uji Mann-Whitney menunjukkan rerata waktu penutupan luka insisi kelompok II ialah 9,7 hari, sedangkan pada kelompok I 12,7 hari (nilai p=0,0000855). Simpulan penelitian ini ialah terdapat pengaruh bermakna dari ekstrak jintan hitam terhadap waktu penutupan luka insisi pada punggung mencit Swiss Webster yaitu terjadi penutupan luka sempurna paling cepat pada hari ke-8.Kata kunci: ekstrak jintan hitam; waktu pentupan luka